2012
DOI: 10.1016/s1413-8670(12)70273-8
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and sensitivity to antibiotics of bacteria isolated from the lower respiratory tract of ventilated patients hospitalized in intensive care units

Abstract: This research corroborated that these nosocomial infections are a relevant medical problem in our context. The most prevalent bacterial infections in the lower respiratory tract of ventilated patients were by Acinetobacter spp., Pseudomonas spp. and Klebsiella spp. The panel of antibiotics used as preventive therapy was not the solution of infections and probably induced drug-resistance mechanisms in these isolated microorganisms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
1
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(3 citation statements)
references
References 25 publications
1
1
1
Order By: Relevance
“…Different studies have reported different values for the cytotoxicity of probiotics. Shahid et al reported a cytotoxicity rate of approximately 28%, which was higher than that of the present study [ 34 ], whereas other studies found a cytotoxicity rate of less than 10% [ 35 , 36 ].…”
Section: Discussioncontrasting
confidence: 90%
See 1 more Smart Citation
“…Different studies have reported different values for the cytotoxicity of probiotics. Shahid et al reported a cytotoxicity rate of approximately 28%, which was higher than that of the present study [ 34 ], whereas other studies found a cytotoxicity rate of less than 10% [ 35 , 36 ].…”
Section: Discussioncontrasting
confidence: 90%
“…On the other hand, L. rhamnosus strains were reported as potentially useful probiotic bacteria against these pathogenic strains. Similar to the previous studies, P. aeruginosa strains were frequently isolated from respiratory samples [ 36 ]. Ahmed et al reported that most cases of isolated P. aeruginosa were detected in respiratory samples.…”
Section: Discussionsupporting
confidence: 76%
“…Superinfections in combination with viral respiratory infections are commonly caused by the above-mentioned microorganisms in patients hospitalized or maintained on mechanical ventilation for a prolonged period [11]. Underlying comorbidities are also a risk factor for co-infections among people of all age groups [12, 13].…”
Section: Introductionmentioning
confidence: 99%